2013
DOI: 10.4236/jpee.2013.17001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Geometric Quality of Weld Beads in the Joining of Carbon Steel Pipelines with Single Pass

Abstract: This work presents the uncertainty evaluation associated with the measurement of linear parameters that define the weld geometry, specifically the width, using a profile projector, in order to meet the current technical standards. The following steps were proposed and implemented: identification of linear parameters that define the weld geometry; identification and study of variables that affect the measurement of these parameters; the adoption of the mathematical model to estimate the uncertainty; planning an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…1. Various studies have shown that the weld bead geometry and behavior has a great impact on the resulting residual stress [60][61][62]. This may explain the decrease into the compressive region in the hoop stress component measured by CM in the clad layer.…”
Section: Comparison Of Through-thickness Residual Stressmentioning
confidence: 99%
“…1. Various studies have shown that the weld bead geometry and behavior has a great impact on the resulting residual stress [60][61][62]. This may explain the decrease into the compressive region in the hoop stress component measured by CM in the clad layer.…”
Section: Comparison Of Through-thickness Residual Stressmentioning
confidence: 99%